2003
DOI: 10.1097/00004872-200309000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour ambulatory blood pressure in community-dwelling elderly men and women, aged 60???102 years

Abstract: Ambulatory blood pressure levels in healthy, community-dwelling 'old elderly' are higher than those reported for younger adults and reflect the prominent age-related rise in SBP associated with advanced old age. Advanced old age is associated with a diminished nocturnal dip in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Our results in a larger population support the finding that men have a higher BP than women, and extend them to obese patients. In general, BP is higher in men than in women below the age of 59 years (the age group of most of our patients), and similar 15 or even greater in women after menopause. 7,8 Kotsis et al 16 found a significantly increased BP assessed by ABPM in a large population of obese patients compared to subjects with normal weights.…”
Section: Discussionmentioning
confidence: 48%
“…Our results in a larger population support the finding that men have a higher BP than women, and extend them to obese patients. In general, BP is higher in men than in women below the age of 59 years (the age group of most of our patients), and similar 15 or even greater in women after menopause. 7,8 Kotsis et al 16 found a significantly increased BP assessed by ABPM in a large population of obese patients compared to subjects with normal weights.…”
Section: Discussionmentioning
confidence: 48%
“…This cross-sectional study cannot determine whether the association between nondipping and PWV is a cause or effect relationship, although both conditions appear to share certain risk factors, such as altered sympathoadrenal activity [28,29] and raised inflammatory markers [30,31]. Both PWV and the prevalence of nondipper status become more common with increasing age [1,10,32], suggesting that they may both reflect a progression to end-organ damage. In prospectively studied type-1 diabetic adolescents, loss of the nocturnal dip preceded the development of microalbuminuria, suggest-ing that nondipping may be an early indicator of risk [33].…”
Section: Discussionmentioning
confidence: 99%
“…26 Experience from a previous study involving very elderly subjects indicated that healthy subjects in this age group commonly had conventional SBP levels Ͼ140 mm Hg. 27 Indeed, SBP levels Ͻ140 mm Hg in the very elderly have been associated with frailty and illness rather than "healthy ageing." 4,28 Recruitment of an age-matched control group required recognition of the age-associated rise in SBP and setting a higher threshold for NT.…”
Section: Discussionmentioning
confidence: 99%